Should World Music Teachers Teach World Music? Popular Music and the World Music Survey Course - Killick, Andrew (Journal of World Popular Music, 2014)
The teaching of “world music” in Western academic institutions has historically focused on traditional musics studied in relation to the cultures that produced them, but often in isolation from other musical cultures and from global processes of cultural exchange and power relations. Since the 1980s, however, the term “world music” has been adopted by the music industry as a marketing category that includes “hybrid” and popular musics which obviously result from such processes. This paper surveys the responses of “world music” educators, as reflected in published teaching materials, to the question of how to handle the industry’s kind of “world music”. It argues for a “transcultural” approach in which “world music” courses would embrace literally any kind of music on an equal footing and situate all music within a single shared history. Finally, it describes an example from my own teaching practice of how such an approach might be realized.